Consistency Between Teaching Practice and the Evaluation of Teaching by Students in Higher Education: Case Studies in the Universidad Veracruzana - Silva Blanco, Lily Ariadna (2023)
There is a solid relationship between educational quality and the quality of teaching offered at universities; therefore, special importance is given to the evaluation of teaching performance. Thus, the objective of this paper is to determine if there exists a congruence between the teaching practice, the perception of the student population, and the grade assigned in the evaluation of teaching by the students. Regarding the approach, the investigator used the qualitative one complemented, in turn, by the quantitative one, as well as descriptive research and case study. For its part, the sample consisted of 10 teachers and 10 students from the academic areas included in the Universidad Veracruzana (UV). Likewise, the researcher collected information from classroom observations and open interviews to later analyze it through a congruence matrix. This is how it was found the lack of consistency between the qualification that the teaching staff obtains in the performance evaluation and their practice in the classroom, taking as a reference the activities that the evaluation instrument of the Programa de Estímulos al Desempeño del Personal Académico (PEDPA) of the UV values. The absence of consistency lies in the perception of the students and in the assessment elements that the evaluation instrument does not consider, for the teaching staff puts into practice greater knowledge, skills, and attitudes than those evaluated, where affective attributes, interpersonal relationships, and personal characteristics stand out. Therefore, these findings show the need to create a teacher evaluation system that includes various techniques such as self-assessment, feedback, observations, peer evaluation, among others, that allow for a more effective evaluation of teacher performance.